Prosthodontic rehabilitation of an edentulous maxilla opposing natural mandibular teeth: a preventive approach to Kelly’s Syndrome: Prosthodontic rehabilitation of an edentulous maxilla opposing natural mandibular teeth: a preventive approach to Kelly’s Syndrome - Sudarman, Ian Afifah; Polanunu, Siti Magfirah Ali; Ikbal, Muhammad; Jubhari, Eri Hendra (Makassar Dental Journal, 2025)
Rehabilitation of an edentulous upper jaw that contacts natural lower jaw teeth poses unique prosthodontic challenges due to uneven load distribution. If not managed properly, this biomechanical imbalance can lead to Kelly Syndrome. A 55-year-old wo-man presented to Hasanuddin University Dental Hospital with the primary complaint of difficulty chewing and reduced self-con-fidence due to extensive tooth loss, but had never used dentures. Intraoral examination revealed total edentulism in the upper jaw and posterior tooth loss in the lower jaw, with teeth 33, 32, 31, 41, 42, and 43 remaining. The posterior alveolar bone of the lo-wer jaw was relatively flat, and there was enlargement of the maxillary tuberosity. The patient reported no relevant systemic disea-ses. The patient sought prosthetic rehabilitation to restore chewing function and improve aesthetics. It was concluded that a com-bination of a metal framework, functional impressions using a modified impression technique, and carefully designed lingual oc-clusion together provide optimal tissue support, stability, and load distribution, as well as prevention against the development of Kelly Syndrome.